2018
DOI: 10.1038/s41385-018-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells

Abstract: Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression of vFlip disrupts tissue homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…In accordance to our previous study [6], all control mice survived the indicated time period of treatment whereas all cFlip iΔIEC mice showed dramatic weight loss and died within 5 days (Fig 2A and 2B). As expected, all of the vFlip iIEC-tg mice survived, as even mice with a constitutive vFlip expression in IECs were viable [16]. Strikingly, cFlip iΔIEC x vFlip iIEC-tg mice were characterized by a significantly higher survival rate as compared to cFlip iΔIEC mice and most of the animals could recover from severe body weight loss around day 8 (Fig 2A and 2B).…”
Section: Vflip Expression Restores the Phenotype Induced By Cflip Delsupporting
confidence: 73%
See 4 more Smart Citations
“…In accordance to our previous study [6], all control mice survived the indicated time period of treatment whereas all cFlip iΔIEC mice showed dramatic weight loss and died within 5 days (Fig 2A and 2B). As expected, all of the vFlip iIEC-tg mice survived, as even mice with a constitutive vFlip expression in IECs were viable [16]. Strikingly, cFlip iΔIEC x vFlip iIEC-tg mice were characterized by a significantly higher survival rate as compared to cFlip iΔIEC mice and most of the animals could recover from severe body weight loss around day 8 (Fig 2A and 2B).…”
Section: Vflip Expression Restores the Phenotype Induced By Cflip Delsupporting
confidence: 73%
“…These cytokines could further activate other signaling pathways beside NFκB, that regulate cFlip expression in cells adjacent to epithelial cells. Beside constitutive activation of NFκB, constitutive expression of vFlip in IECs moreover induced the spontaneous development of intestinal inflammation accompanied by Paneth cell loss and increased epithelial cell death [16]. However, the phenotype of vFlip IEC-tg mice was not completely identical to mice with a constitutive activation of NFκB in IECs [30,31], which were not characterized by increased cell death.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations